Management of female para-urethral cyst with dyspareunia: a case report - Manoj Kumar Deepak; R. M. Meyyappan; T. Senthil Kumar; J. Saravanan (Journal of Medical Case Reports)
Abstract Background The diagnosis and management of female genital conditions (Rodriguez et al. in Clin Anat 34(1):103–107, 2020. https://doi.org/10.1002/ca.23654 ) are often challenging. The atypical presentations, combined with patient hesitancy to be subjected to an examination by a male urologist, are factors that limit a timely diagnosis. Para-urethral cysts (Pastor and Chmel in Int Urogynecol J 29(5):621–629, 2018. https://doi.org/10.1007/s00192-017-3527-9 ) are often incidentally detected by gynecologists during pelvic examination for other reasons. Patients rarely present with complaints of lower urinary tract symptoms and dyspareunia affecting sexual life. Diagnosis in most instances can be made by physical examination but often a detailed evaluation with ultrasonography, voiding cystourethrogram, computed tomography, or magnetic resonance imaging is needed. The definitive management of symptomatic para-urethral cysts is through surgical excision. Objective This report aims to reflect clinically upon a rare pathology of the female genital system. Case presentation We present the case of a 36-year-old, sexually active, Indian (Asian) woman with a 6-month history of progressively worsening lower urinary tract symptoms, consisting of dysuria, post-micturition dribble, increased urination frequency, and significant dyspareunia. Physical examination in the lithotomy position revealed a cystic lesion located in the midline slightly to the left of the anterior vaginal wall. Magnetic resonance imaging also revealed a T2/T1 hyperintense lesion located below the level of the pubic symphysis. The patient was posted for exploration under anesthesia and the cyst was excised completely. The histopathology findings were consistent with para-urethral gland cyst with ulceration and squamous metaplasia. Conclusion Any lower urinary tract symptoms in a woman needs thorough clinical examination. Association of para-urethral cyst with lower urinary tract symptoms and dyspareunia is rare, and if present, always warrants surgical excision.